PERSEPSI LULUSAN DIII KEPERAWATAN TENTANG UJI KOMPETENSI PERAWAT DI STIK STELLA MARIS MAKASSAR - Asrijal Bakri (Jurnal Keperawatan Florence Nightingale, 2018)
Nurse competencies test as a screening process to ensure registered nurses and have the required competence . But now there are many students who had followed the competency test is often anxiety, worry, stress, and having difficulty doing about as prepared brief and limited time. The purpose of this study was to determine the competency test understanding, competency testing purposes, the impact of the competency test, barriers experienced during the competency test and the preparations made prior competency test .Research conducted using qualitative design with phenomenology . Technique intake of participants in this study using techniques nonprobability sampling is purposive sampling. Participants in this study were 8 people. Data were collected using a triangulation technique that is open and structured interviews, observation, and documentation. Test the validity of the data was conducted on the test the credibility, transferability test, and test depanability. The data analysis was conducted by Miller and Huberman. The results showed (1) understanding the competency test is the measurement of the ability of the nurse who visits the knowledge, skills and attitudes which passed the nurses will get STR. (2) The purpose of the nursing profession competency test is to be recognized and able to work in accordance with national standards. (3) The positive impact or excess is passed the competency test means are entitled to STR. While the weakness if not pass the competency test means it will not acquire STR. (4) Barriers experienced graduates Stella Maris Nursing DIII is the amount of time involved in completing a very short question. (5) Preparation of the face of the competency test is studying, praying, trying to continue to seek information related to the competency test early on, making it easier to solve problems at exam time.